The Diagnostic Value of Serum Ferritin for Telogen Effluvium: A Cross-Sectional Comparative Study - Cheng T; Fang H; Wang Y; Wang Y; Yang Z; Wu R; Yang D (Dove Medical Press, 2021)
Tiantian Cheng,1,2 Huijuan Fang,1,2 Yongchao Wang,3 Ying Wang,2 Zhishan Yang,1,2 Ruiying Wu,1,2 Dingquan Yang2 1School of Clinical Medicine, Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 2Department of Dermatology, China-Japan Friendship Hospital, Beijing, People’s Republic of China; 3Department of Clinical Laboratory, China-Japan Friendship Hospital, Beijing, People’s Republic of ChinaCorrespondence: Dingquan YangDepartment of Dermatology, China-Japan Friendship Hospital, Beijing, People’s Republic of ChinaTel +86 13901218671Email ydqlx@163.comPurpose: This study aimed to explore the relationship between serum ferritin levels and telogen effluvium.Patients and Methods: A total of 193 telogen effluvium patients and 104 female androgenetic alopecia patients were included. We collected the test result of serum ferritin levels, compared with the results of 183 healthy subjects. Receiver Operator Characteristic curves were generated to assess the potential diagnostic value of serum ferritin in telogen effluvium patients.Results: The serum ferritin in telogen effluvium patients were significantly lower than that in the healthy control group (P = 0.000) or female androgenetic alopecia patients (P =0.000). Patients with lower serum ferritin levels got high odds to have telogen effluvium. The areas under the Receiver Operator Characteristic curve of serum ferritin levels were 0.735 and 0.645 for distinguishing telogen effluvium patients from healthy control subjects or female androgenetic alopecia patients.Conclusion: Serum ferritin could be a potential biomarker for clinical diagnosis of telogen effluvium.Keywords: serum ferritin, telogen effluvium, female androgenetic alopecia, ROC curve